Implantation of rectosigmoid cancer in a preexisting anal fissure - Sato, Harunobu (Int Cancer Conf J, 2021)
Colorectal cancer (CRC) rarely spreads by implantation. We report a case of implantation of rectosigmoid cancer in an anal fissure. A 70-year-old woman with a 15-year medical history of anal fissure was referred to our hospital with anal pain of 3-month duration. Colonoscopy revealed a rectosigmoid tumor and a 10-mm submucosal tumor at the anal verge. Biopsy of the rectosigmoid and anal tumors revealed that both were moderately differentiated adenocarcinomas, and abdominoperineal resection (APR) was performed. The anal adenocarcinoma was surrounded by squamous cell epithelium and mainly proliferated in the submucosal and muscular layers. The patient was diagnosed as having rectosigmoid cancer with implantation of cancer in a preexisting anal fissure. The patient remains well 43 months post-surgery with no sign of recurrence. Implantation of CRC in anal fissure is a rare occurrence. Nevertheless, performing adequate anal examination of patients with CRC before surgery and during follow-up is necessary. Further, it is important to perform preoperative large bowel examination of patients with benign anal diseases to prevent implantation of CRC.